A168 HEALTH-RELATED QUALITY OF LIFE IN WOMEN WITH INFLAMMATORY BOWEL DISEASE: FROM PRECONCEPTION TO POSTPARTUM. (4th March 2021) - Wang, G; Rodriguez, N; Ambrosio, L; Tandon, P; Huang, V W
Abstract: Background: Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), impacts health-related quality of life (HRQoL). In pregnancy and postpartum, distinguishing IBD-specific symptoms is challenging. The extent to which pregnancy and disease activity affects HRQoL in IBD patients remains unknown. Aims: To assess women with and without IBD at pre-, intra-, and postpartum timepoints, and examine the impact of pregnancy, IBD type, and disease activity on IBD-related HRQoL. Methods: Preconception (PC) and pregnant women aged ≥18 years with and without IBD completed surveys at various timepoints from PC to 12 months postpartum (PP). The Short IBD Questionnaire (SIBDQ) is a validated survey that assesses HRQoL in IBD patients and covers bowel, emotional, systemic, and social domains; a higher score indicates a better HRQoL. Participants completed SIBDQ and modified Harvey Bradshaw Index (mHBI) for CD or partial Mayo score (pMayo) for UC. Clinically active disease was defined as mHBI ≥5 or pMayo ≥2; objectively active disease was defined as C-reactive protein (CRP) ≥8.0mg/L or fecal calprotectin (FC) ≥250mg/kg. Continuous variables were analyzed by the t-test whereas categorical variables were assessed by the chi-squared test, with p<0.05 suggestive of statistical significance. Results: 61 patients with IBD (36 UC, 25 CD) and 12 healthy controls were included. In IBD patients, SIBDQ was positively associated with income during PC, but not once patients became pregnant. No association was found with education level. There were no significant differences in mean SIBDQ between study timepoints. SIBDQ was significantly lower in IBD patients with clinically active disease at all trimesters of pregnancy and all PP timepoints, but not at PC. SIBDQ was significantly lower in patients with high CRP during trimester 1 (T1), but not later in pregnancy. Generally, SIBDQ was lower in patients with higher FC; SIBDQ bowel scores were significantly lower in patients with high FC at T2, T3, and PP6. During PC, SIBDQ was significantly higher in UC patients than CD patients; this difference was lost in pregnancy. During PP, SIBDQ bowel and social scores were significantly lower in UC patients than CD patients at 6 months. Compared to healthy controls, IBD patients had significantly lower SIBDQ at PC, T1, and T2; they also had significantly lower SIBDQ bowel scores in early PP, which resolved by 12 months. In IBD patients, no association was found between PP SIBDQ scores and breastfeeding or delivery method. Conclusions: Women with IBD experience worse HRQoL in early pregnancy, and worse bowel-related HRQoL postpartum. UC patients have better PC HRQoL but suffer worse postpartum bowel-related HRQoL than CD patients. Overall, SIBDQ correlates well with clinical and biochemical disease activity during pregnancy and postpartum. Funding Agencies: Women and Children's Health Research Institute (WCHRI), Centre of Excellence for Gastrointestinal Inflammation and Immunity Research (CEGIIR), University of Alberta Faculty of Medicine